Unveiling measurement precision of Indonesian version DASS-21: A rating scale model - Natanael, Yonathan; Fridayanti (University of Muhammadiyah Malang, 2026)
Testing on the structure factor of the Indonesian version of Depression Anxiety Stress Scale (DASS)-21 has been carried out using confirmatory factor analysis. To prove the quality of the psychometric properties of DASS-21 in more detail, this study aims to evaluate the internal validity and reliability of the Indonesian version of DASS-21 using the Rasch rating scale model. This research approach uses a cross-sectional design, and to get as many as 424 undergraduate students age ranged from 17 to 26 years old (Mage = 20.49 and SD = 1.79) in various regions in Indonesia, the researcher uses convenience sampling. The results show that the Indonesian version of DASS-21 is unidimensional even though it is tested on each subscale or as a whole. It has an excellent reliability index, all items used are fit, and the use of four answer choices is appropriate, but identified as many as 6 of the 21 items detected experiencing a differential item functioning that shows the weaknesses of the Indonesian version of DASS-21. Psychometrically, only 15 of the 21 items from the Indonesian version of DASS-21 are recommended for measuring psychological distress in Indonesia.